Socialization of Making RAB for Infrastructure Development in Lau Gumba Village - Asri Afriliany Surbakti; Yunita Eriyanti Pakpahan; Dina Indah Permatasari; Aroli Harefa; Hosea Tarigan; Enjellia Noventin Br Tarigan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The village government receives Village Funds from the central government, part of which is used for infrastructure development in the village. In order for construction to be carried out in villages, it was previously planned that the amount of funds needed so that the infrastructure development funds could be transferred by the central government to village accounts. The amount of planned costs is called the budget plan (RAB). Considering that every year there are infrastructure developments originating from village funds, every year an RAB is also made, in which most of the village infrastructure RAB is designed by a third party (consultant). It's a good idea for the village community to be able to make RAB in order to reduce the cost of hiring consultant services to make RAB, so that the costs previously allocated for hiring third party services can be converted to other village activities